Treatment with high-flow oxygen therapy in asthma exacerbations in a paediatric hospital ward: Experience from 2012 to 2016 - Felipe González Martínez; María Isabel González Sánchez; Blanca Toledo del Castillo; Jimena Pérez Moreno; María Medina Muñoz; Cristina Rodríguez Jiménez; Rosa Rodríguez Fernández (Elsevier, 2019)
Objective: To assess the experience with oxygen therapy with a high flow nasal cannula (HFNC) in hospital on patients with asthmatic exacerbation (AE) in a paediatric ward, and to assess the clinical outcome according with the initial oxygen flow (15 lpm or <15 lpm). Methods: This was a retrospective study of children aged 4-15 years with AE admitted to a paediatric ward in a tertiary level hospital between 2012 and 2016. Two groups of patients were compared; Group 1: patients treated with HFNC, and Group 2: patients treated with conventional oxygen therapy. A logistic regression model was constructed in order to identify predictive variables of HFNC. The clinical outcome of the patients was also compared according to the initial flow of HFNC (15 lpm vs. <15 lpm). Results: The study included a total of 536 patients with AE, 40 (7.5%) of whom required HFNC. The median age was 5 (4-6) years. Heart rate (HR), respiratory rate (RR) and pulmonary score (PS) significantly decreased at 3-6 h after starting HFNC in Group 1. In the multivariate analysis, patients with high pulmonary score values and greater number of previous admissions required HFNC more frequently. Patients treated with an initial flow of 15 lpm were admitted less frequently to the PICU than those with an initial flow less than 15 lpm (13% vs. 47%, P = .05). Conclusion: HFNC seems to be a useful therapy for asthma exacerbation in paediatric wards. Severity of pulmonary score and the number of previous admissions could enable a risk group that needs HFNC to be identified. Resumen: Objetivo: Analizar la experiencia de tratamiento con OAF en pacientes ingresados por crisis asmática (CA) en una planta de hospitalización pediátrica (PHP), así como analizar la diferencia de la evolución según sean tratados de entrada con flujos de 15 lpm o inferiores a 15 lpm. Métodos: Estudio retrospectivo y analítico en niños (4 a 15 años) ingresados por CA en la PHP de un hospital terciario entre 2012 y 2016. Se compararon 2 grupos de pacientes: los tratados con OAF y los tratados con oxigenoterapia convencional; se construyó un modelo de regresión logística para identificar variables predictivas de necesidad de OAF. Se comparó la evolución de los pacientes en función del flujo de inicio de la OAF (15 lpm vs <15 lpm). Resultados: Se incluyeron 536 pacientes con CA, de los que 40 (7,5%) precisaron OAF. La mediana de edad fue de 5 (4-6) años. La OAF en los pacientes con CA produjo una reducción en la frecuencia cardiaca, frecuencia respiratoria y Pulmonary Score en las primeras 3-6 horas de tratamiento. En el análisis multivariante los pacientes con una mayor puntuación en el PS y un mayor número de ingresos previos precisaron con más frecuencia OAF. Los pacientes tratados con un flujo de inicio de 15 lpm ingresaron menos frecuentemente en UCIP que aquellos con flujo inicial inferior a 15 lpm (13% vs. 47%, p = 0,05). Conclusión: La OAF como tratamiento de las CA en las PHP parece ser una terapia de gran utilidad. El Pulmonary Score y el número de ingresos previos permite identificar un grupo de riesgo de precisar OAF.